LINGUISTIC ANALYSIS OF THE NAMES OF APPLE TREES, THEIR FRUITS AND VARIETIES (BASED ON THE COLLOQUIAL VOCABULARY OF THE MIDDLE BUG AREA) - Polishchuk, Svitlana (Linguistic Bulletin (Movoznavchyi Visnyk), 2024)
Introduction. Ukrainians are particularly fond of growing fruit trees. Apricot, cherry, peach, plum, apple and other orchards have long been and still remain the decoration of the village and the pride of their owners. This made it possible to preserve a rich gardening vocabulary in the examined dialects. The purpose. The purpose of the research is to carry out a multi-level linguistic analysis of floranomens for apple trees, their fruits and varieties, documented in the Eastern Podillia and Western Steppe dialects of the Middle Bug area. The methods. The article uses general scientific methods of research: analysis, synthesis and observation, which made it possible to identify and systematize the colloquial material. The descriptive method was used in the analysis of vernacular speech. The expeditionary method and the methods of questionnaires and interviews contributed to the documenting of colloquial speech. Contextual and interpretive analysis allowed to identify transformations of the semantic scope of lexemes functioning in the speech of dialect speakers. The linguogeographical method made it possible to illustrate the areology of the documented names. Main results of the study. Originality. Colloquial texts presented in the form of transcriptions, which attest phonetic, accentual, word-forming, lexical, morphological, syntactic, and other features of dialectal language, have been introduced into scientific circulation. At the same time, original samples of vernacular, valuable in terms of dialectology, phonetics, lexicology, grammar, ethnography, gardening, breeding, cooking, etc. are presented. Conclusions and specific suggestions of the author. More than 118 floranomens (counting phrases, diminutive forms and phonetic variants of some words) have been documented and introduced into scientific use, including 85 phytonyms. A multi-level linguistic analysis of these names was carried out, in particular, their phonetic, accentuation, lexical-semantic, morphological, syntactic features were taken into account; the motivation and etymology of most of the names were clarified; their spatial distribution is presented. The prospect of further research is in the continuation of the analysis of floranomens for the designation of fruit trees that belong to the rose family (Rosaceae) in the dialects of the specified area.